Stability Test Of Miana Leaf Extract (Coleus Atropurpureus) With The Addition Of Glycerol In The Diagnosis Of Parasitic Infections - Yeli Hartuti; Karolina Rosmiati; Miftah Arrifah (LPPM Akafarma Sunan Giri Ponorogo, 2026)
Worm infections (Helminthiasis) are among the most common infections affecting children. Worm infections caused by soil-transmitted helminths result from contact with the eggs or larvae of these parasites, which develop in moist soil. One method for detecting parasitic worm infections is the Direct slide method using 2% eosin. Miana leaves (Coleus atropurpureus) are plants that contain anthocyanin pigments, producing purple, red, or blue colors, so extracts from miana leaves can be used in the identification of Soil Transmitted Helminth eggs. However, the stability and effectiveness of miana leaf extracts during storage are currently unknown. This study aims to determine the storage stability of miana leaf extract at 2–6°C with the addition of 0.5% and 1% glycerol in the diagnosis of helminth infections. This is a true experimental study with a post-test control design. Miana leaf extract was obtained through a maceration process using distilled water and 2% acetic acid (1:7) as solvents. Glycerol 0.5% and 1% were then added to the miana leaf extract, which was stored at 2–6°C and tested for staining stability on days 0, 5, 10, and 15. The results of the study on day 0 showed a score of 3 for all treatments. The extract without glycerol showed a decrease in stability on day 5 and onwards, as did the extract with the addition of 0.5% glycerol, which showed a decrease in stability on day 10 and onwards, while the addition of 1% glycerol maintained color stability until day 15. The results of the study can be concluded that the addition of 1% glycerol effectively maintains the stability of miana leaf extract for 15 days at a temperature of 2–6°C in the diagnosis of helminth infection .